Ask Question
9 June, 05:19

Arrange the equations in the correct sequence to find the inverse of f (x) = y=x-4/33-x?

equations: (only 6 out of the 9 equations are used)

1) 33x - xy = y - 4

2) 33x + 4 = y (1 + x)

3) 33x - xy = y + 4

4) 33x + 4 = y + xy

5) y = f^-1 (x) = 1+x / 33x+4

6) 33x - xy = y+4

7) x = y-4 / 33-y

8) y = f^-1 (x) = 33x+4 / 1+x

9) x (33 - y) = y-4

+3
Answers (1)
  1. 9 June, 05:51
    0
    To find the inverse of the function, first is to replace every x with a y and all y with x's.

    That is,

    x = y-4/33-y (Equation no. 7)

    We solve y of the equation above by the steps below.

    x (33 - y) = y - 4 (Equation no. 9)

    33x - xy = y - 4 (Equation no. 1)

    33x + 4 = y + xy (Equation no. 4)

    33x + 4 = y (1 + x) (Equation no. 2)

    Then, lastly,

    y = f⁻¹ (x) = (33x + 4) / (1 + x) (Equation no. 8)

    Therefore, the arrangement of the equations is Equations 7, 9, 1, 4, 2, and 8.
Know the Answer?